A simulated patient study to evaluate community pharmacist assessment, management and advice giving to patients with asthma - Sanah Hasan; Lujain Al Oum; Nageeb AbdulGalil Hassan (Taylor & Francis Group, 2021)
Background Research has shown that there is an increase in the global prevalence of asthma. Pharmacists are well positioned to screen and refer patients for better management of asthma. This study aimed to evaluate community pharmacists' ability to assess the 3 C's (Control, Compliance, Complications) and offer Management and Advice for patients with asthma in the UAE. Methods Three fifth year pharmacy students role played a mystery shopper visiting community pharmacies and requesting symptom relief from uncontrolled asthma. Incidence of cough syrup and reliever inhaler supply, physician referral rate, correction of inhaler technique, and counseling on the medications, adherence to the medications and adverse drug reactions were calculated. Results One hundred, ninety five pharmacies were visited, 27% of pharmacists asked about the need for cough syrup and 60% asked about the need for albuterol inhaler. Only 26% asked about other medications. Less than 20% assessed inhaler technique, only one pharmacist asked about regular use of preventer medications and if the patient was adhering to them and only 16% asked about side effects from medications. Most pharmacists (67%) supplied at least one of the medications, while 65% referred the patient to a physician. Only 21% gave information about correct inhaler technique, the majority (> 60%) being incomplete, only 16 pharmacists gave information about asthma and its triggers; the majority (63%) being incomplete. One third of the pharmacists counselled the patient on the medications with one giving complete information. Conclusions The study highlighted suboptimal assessment of control, compliance to preventer medications and complications of asthma and the medications that treat it. It also highlighted suboptimal Management and Advice giving and counseling on medication use by pharmacists. Training pharmacists in all aspects of asthma handling is clearly indicated. Despite the high rate of correct patient referral to a physician noted in this study, there is risk to it, as patients might not actually go to see their physician and continue to depend on symptom relief for the management of their asthma. This study highlighted the importance of improving patient education and information seeking attitude.